2020
DOI: 10.1097/psy.0000000000000867
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Financial Strain and Emotional Well-Being With Physiological Responses to Acute Mental Stress

Abstract: This manuscript has been accepted by the editors of Psychosomatic Medicine, but it has not yet been copy-edited; information within these pages is therefore subject to change. During the copy-editing and production phases, language usage and any textual errors will be corrected, and pages will be composed into their final format.Please visit the journal's website (www.psychosomaticmedicine.org) to check for a final version of the article.When citing this article, please use the following: Psychosomatic Medicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…A central implication of this study is that financial stressors were most relevant to the health of people who identified financial security as important to their well-being. People who value financial security may appraise financial stressors as particularly threatening, aligning well with stress appraisal theory (18). Notably, the importance of financial security was not independently associated with mortality.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…A central implication of this study is that financial stressors were most relevant to the health of people who identified financial security as important to their well-being. People who value financial security may appraise financial stressors as particularly threatening, aligning well with stress appraisal theory (18). Notably, the importance of financial security was not independently associated with mortality.…”
Section: Discussionmentioning
confidence: 84%
“…The importance and salience of financial stressors are also likely to play a role in the health relevance of financial stressors. Stress appraisal theory (18) highlights the importance of people's cognitive appraisals in their responses to stressful life events. When stressors are appraised as more threatening or people feel unable to cope with a stressor, they are particularly damaging to people's mental and physical well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Debt in our study was, in contrast, significantly associated with poor health. The link between financial strain and poor health is well-established in the international literature (Artazcoz et al 2021 ; Prentice et al 2017 ; Steptoe et al 2020 ). Several hypotheses have been put forward to explain this link: lower financial resources may decrease access to healthcare, utilization of healthcare services and treatment adherence (Grafova 2018b ).…”
Section: Discussionmentioning
confidence: 97%
“…Such stressors are, for example, financial obligations for family members or being in debt. Financial strain has been linked to health outcomes, such as poor self-reported health (Artazcoz et al 2021 ; Prentice et al 2017 ), poor mental health (Steptoe et al 2020 ), and poor sleep (Hall et al 2009 ; Steptoe et al 2020 ) across international studies. With respect to RMG workers in Bangladesh, qualitative research suggests that workers worry about not earning enough money to financially support their families (Akhter et al 2017b ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past half century, numerous studies, literature reviews, and meta-analyses have linked unemployment with poorer mental health (Brand, Levy, and Gallo 2008; Brand 2015; Burgard, Brand, and House 2007; Burgard and Kalousova 2015; Crowe, Butterworth, and Leach 2016; Dooley, Catalano, and Wilson 1994; Ezzy 1993; Fenwick and Tausig 2007; Gore 1978; Kessler, House, and Turner 1987; Lennon and Limonic 2009; Liem and Liem 1978; Miller and Hoppe 1994; Milner, Page, and LaMontagne 2014; Steptoe, Emch, and Hamer 2020; Strandh et al 2014; Warr 1987; Warr, Jackson, and Banks 1988). While the association between unemployment and mental health is clearly bidirectional, cross-sectional and longitudinal analyses from around the world and across research disciplines (e.g., economics, psychology, public health, and sociology) and different periods of instability (e.g., during recessions) have consistently shown that people who experience unemployment tend to exhibit higher rates of anxiety, depression, somatization, non-specific psychological distress, and suicidal behavior.…”
Section: Introductionmentioning
confidence: 99%